2017
DOI: 10.4172/2157-7579.1000489
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus albidus var. albidus Isolated from Turquoise-Fronted Parrots (Amazona aestiva: Psittacidae) Kept in Captivity: A Probable Reservoir Ecological of Fungal Specimen

Abstract: Cryptococcus is an opportunistic yeast that causes life-threatening infections as meningoencephalitis primarily in immunocompromised hosts, generally associated with AIDS. The source of this organism is mainly pigeon excreta; however, other avian species' excreta are implicated as a source of this yeast. The aim of this study was to perform the isolation of yeasts of the Cryptococcus genus from the cloacae of 40 parrots kept in captivity area of the genus Amazona aestiva. These birds were anesthetized, the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…In contrast to the findings of Nascimento et al (2017), considering the droppings of the same species (Amazona aestiva) housed at the UFMT zoological garden, C. albidus was not isolated, but the presence of yeasts (Pichia anomala, Candida krusei and Trichosporon spp) was observed, together with other genera of filamentous fungi. Pereira (2006) reported the isolation of Cryptococcus neoformans in Aratinga mitrata residing at a zoo.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…In contrast to the findings of Nascimento et al (2017), considering the droppings of the same species (Amazona aestiva) housed at the UFMT zoological garden, C. albidus was not isolated, but the presence of yeasts (Pichia anomala, Candida krusei and Trichosporon spp) was observed, together with other genera of filamentous fungi. Pereira (2006) reported the isolation of Cryptococcus neoformans in Aratinga mitrata residing at a zoo.…”
Section: Discussioncontrasting
confidence: 90%
“…in excreta of psittacine birds (Filiú et al, 2002), members of the orders Passeriformes (Marinho et al, 2010;Lugarini et al, 2008), Columbiformes (Cichon et al, 2011), and Accipitriformes (Cafarchia et al, 2006) has been consistently reported in the literature and often associated with the bird's habit of scraping and fragmenting pieces of wood and branches (Filiú et al, 2002). Nascimento et al (2017) recorded the occurrence of yeasts belonging to the Cryptococcus complex (C. albidus var. albidus = C. albidus) in the cloacae of 40 parrots (Amazona aestiva) maintained in a private farm located in the City of Jundiai, São Paulo, Brazil.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Five others, namely, Cryptococcus ovalis , N. chernovii , H. festucosa , F. oeirense , and F. wieringae , were previously isolated from various infected or asymptomatic mammals, such as cats, dogs, or horses, but have not been isolated from any birds [ 40 , 53 , 54 ]. The fourteen remaining species had already been isolated from bird sources but mostly from pigeon droppings [ 55 , 56 , 57 , 58 ] and captive or pet birds [ 59 , 60 , 61 , 62 ]. In fact, very few wild birds have been described as possible sources for RCFC.…”
Section: Discussionmentioning
confidence: 99%